Strategi Kultural Pelestarian Barongan Blora di Kabupaten Blora (Studi Kasus di Sanggar Barongan Risang Guntur Seto) - Kristiana, Reza; Yuhastina, Yuhastina; Rahman, Abdul (International Journal of Demos (IJD), 2022)
AbstractThis research is research that aims to examine the cultural strategies that occur in the art community in preserving the art of Barongan Blora in Blora Regency. The art community referred to in this research is Risang Guntur Seto which is a pilot barongan studio in Blora. The conservation efforts carried out by this studio are a cultural strategy step that through the process can solve the studio problem which is also a problem with Blora Regency to preserve Barongan Blora. By using qualitative research and case studies as an approach, so as to dig up information about cultural strategies for the preservation of barongan in the Risang Guntur Seto studio. The results of the study explained that there were problems faced by Sanggar Risang Guntur Seto which were then solved by 2 steps of cultural strategy, namely the innovation strategy and the relationship strategy. This step makes Barongan Blora remain sustainable in Blora Regency.Keywords: Barongan Blora; Culturan Strategy; Preservation.Â AbstrakPenelitian ini merupakan penelitian yang bertujuan mengkaji strategi budaya yang terjadi pada komunitas seni dalam melestarikan kesenian Barongan Blora di Kabupaten Blora. Komunitas seni yang dimaksud dalam penelitian ini adalah Risang Guntur Seto yang merupakan sanggar barongan percontohan di Blora. Upaya-upaya pelestarian yang dilakukan sanggar ini sebagai langkah strategi kebudayaan yang melalui prosesnya mampu menyelesaikan masalah sanggar yang juga menjadi masalah bersama Kabupaten Blora untuk melestarikan Barongan Blora. Dengan menggunakan penelitian kualitatif dan studi kasus sebagai pendekatannya, sehingga dapat menggali informasi mengenai strategi kebudayaan untuk pelestarian barongan dalam sanggar Risang Guntur Seto. Hasil peneltian menjelaskan ada masalah yang dihadapi Sanggar Risang Guntur Seto yang kemudian diselesaikan dengan 2 langkah strategi kebudayaan yaitu strategi inovasi dan strategi relasi. Langkah tersebut menjadikan Barongan Blora tetap lestari di Kabupaten Blora.Kata Kunci: Barongan Blora; Strategi Kultural; Pelestarian.